Correction: MN15: A Kohn–Sham global-hybrid exchange–correlation density functional with broad accuracy for multi-reference and single-reference systems and noncovalent interactions. Issue 9 (12th July 2016) - Yu, Haoyu S.; He, Xiao; Li, Shaohong L.; Truhlar, Donald G.
Abstract : Correction for 'MN15: A Kohn–Sham global-hybrid exchange–correlation density functional with broad accuracy for multi-reference and single-reference systems and noncovalent interactions' by Haoyu S. Yu et al., Chem. Sci., 2016, DOI: ; Web:10.1039/c6sc00705h .